Pemberian Pakan dengan Kadar Serat Kasar yang Berbeda Terhadap Daya Cerna Pakan pada Ikan Berlambung dan Ikan Tidak Berlambung [Feeding With Different Levels Of Crude Fiber On The Diggestibility Of Feed In True Stomach Fish and Stomachless Fish ] - Muhammad Arief; Ratna Ayu Megawat; Moch. Amin Alamsjah (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract Feed plays an important role in fish farming activities. Meeting the needs of feed quality and quantity sufficient aims to increase farming production, in addition to the feed given to fish properly assessed not only from the composition of the feed but also of how much the components contained in the feed can be absorbed and utilized by the fish in his life. Factors that may affect the digestibility of feed include feed composition, range and quality of the enzyme in the intestine or the stomach of fish (NRC, 1993) while Mudjiman (2002) states that the specific differences in the digestive system in fish can lead to differences in the ability of fish to digest feed, for it is used in this study true stomach fish and stomachless fish. This study aims to determine whether there are differences in the digestibility of crude fiber and determine the optimum content in true stomach fish and stomachless fish. The study design used in this study was Complete Randomized Design (CRD) factorial pattern with two factors, factor A is a type of fish and factor B is the type of feed. Analysis of the data were processed using Analysis of Variance (ANOVA) to determine whether there is an interaction effect between the treatment given. If there is a difference in the effect of test distance followed by Multiple Duncan (Duncan's Multiple Range Test). Based on the research results showed that there is a very real difference (p<0.01) on the digestibility of fish and feed efficiency in true stomach fish and stomachless fish. The highest digestibility resulting in treatment A2 (81,26%) while for fish feed efficiency, the true stomach fish has a higher feed efficiency than the stomachless fish is 20,91%.